Review of available therapies for the treatment of pediatric COVID-19-associated polyarticular inflammatory syndrome - Michał Leśniewski (Kazimierz Wielki University, 2024)
Recently, there have been an increasing number of reports from around the world describing children and adolescents with multisystemic inflammatory conditions associated with COVID-19. The clinical features of these pediatric cases are both similar to and different from other well-described inflammatory syndromes, including Kawasaki disease. Symptoms appear to develop after infection, rather than in the acute phase of COVID-19. Regarding the clinical spectrum, much remains unknown. The new disease entity challenges specialists around the world in developing universal management protocols. In the fight for the health and lives of patients, treatment according to standard protocols for Kawasaki disease has been used. However, further clinical trials are required to prove the effectiveness and safety of these treatments. There are reports of successful therapy using intravenous immunoglobulin preparations and steroid therapy. Biologic, antiviral, antibiotic, antiplatelet and anticoagulant therapies are also used. The described pediatric disease can be associated with hemodynamic failure, so treatment should take place in a hospital setting, under the watchful eye of a multidisciplinary team.